Social networks as an educational tool through scientific production - Lorenzo Lledó, Gonzalo (Revista General de Información y Documentación, 2020)
Today's societies have been evolving towards new forms of communication provided by technology. Social networks have enabled the creation of interactive environments for sharing information and creating knowledge. The influence of these tools in different contexts is being recognized in the scientific literature. Therefore, the objective of this research has been to analyze the scientific production on the use of social networks as training tools during the period 2009-2018. For this purpose, several databases have been used, including the Science Citation Index, Emerging Source Citation Index and Science Citation Index Expanded. A series of key words were introduced that allowed us to obtain a sample of 252 documents that were analyzed according to a series of bibliometric indicators such as the immediacy index, the isolation index or the number of annual publications. The results show that the period of greatest production has been between 2015-2018, with the vast majority of articles published in Q1 journals in both the Social Science Citation Index and the Science Citation Index Expanded. On the other hand, there is a 19% overlap between the journals in both databases. Likewise, the working teams range from one to three authors. As future lines of work, the idea is to complete the sample of documents from a more thematic analysis perspective.
Keywords: social networks; ISI web of Knowledge; information society